2016
DOI: 10.1007/s00464-016-4931-9
|View full text |Cite
|
Sign up to set email alerts
|

A modified Delphi method toward multidisciplinary consensus on functional convalescence recommendations after abdominal surgery

Abstract: BackgroundEvidence-based information on the resumption of daily activities following uncomplicated abdominal surgery is scarce and not yet standardized in medical guidelines. As a consequence, convalescence recommendations are generally not provided after surgery, leading to patients’ insecurity, needlessly delayed recovery and prolonged sick leave. The aim of this study was to generate consensus-based multidisciplinary convalescence recommendations, including advice on return to work, applicable for both pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…A limitation of the study is the heterogeneity of surgical procedures. However, the Delphi study that we performed to compose the convalescence recommendations used in this study showed more or less the same convalescence recommendations for all surgical procedures, which suggests that the recovery periods of these surgical procedures are comparable [24,25]. In addition, the heterogeneity can be considered an advantage, because the results will be applicable to a broader population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…A limitation of the study is the heterogeneity of surgical procedures. However, the Delphi study that we performed to compose the convalescence recommendations used in this study showed more or less the same convalescence recommendations for all surgical procedures, which suggests that the recovery periods of these surgical procedures are comparable [24,25]. In addition, the heterogeneity can be considered an advantage, because the results will be applicable to a broader population.…”
Section: Discussionmentioning
confidence: 86%
“…Using a modified Delphi method, specific convalescence recommendations were developed for several types of abdominal surgical procedures [24,25]. The recommendations given are tailored to the patient and are based on the input of patients’ normal preoperative activities and the surgical technique (using algorithms).…”
Section: Methodsmentioning
confidence: 99%
“…The modified Delphi method can help to fill the knowledge gap by reaching consensus using the knowledge and personal opinions of experts [7,8]. The modified Delphi method typically presents participants with 2-4 rounds of a fixed set of questions.…”
Section: Modified Delphi Methodsmentioning
confidence: 99%
“…It is usually an individual decision, and depends on their occupation and the procedure performed. Patients may only require two weeks away from work after smaller procedures (such as cholecystectomy or appendicectomy) 16 . Following cancer surgery, a longer break, or gradual return to work may be advised, such as light duties or reduced hours 16 .…”
Section: Return To Workmentioning
confidence: 99%
“…Patients may only require two weeks away from work after smaller procedures (such as cholecystectomy or appendicectomy) 16 . Following cancer surgery, a longer break, or gradual return to work may be advised, such as light duties or reduced hours 16 . "Sick notes" are provided by the hospital team to cover the anticipated period of absence.…”
Section: Return To Workmentioning
confidence: 99%